2023
DOI: 10.1021/acscatal.3c05467
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of β-Amino Boronates via Amide α-C–H Bond Activation and C(sp3)–C(sp3) Coupling under Dual Ni/Photoredox Catalysis

Zihao Hu,
Dong Wang,
Tao XU

Abstract: Direct transformations of readily available amines or amides via C−H bond functionalization could provide a fast route for accessing complex molecules. While various groups have been successfully incorporated into the α position of the nitrogen atom with a photoredox system or C−H bond activation, couplings with functionalized alkyl halides are still very challenging. Herein, we report a direct and convenient protocol for accessing β-amino boronates through the C(sp 3 )−C(sp 3 ) coupling of amides and α-bromob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Xu et al 69 reported an effective method for achieving the C(sp 3 )–C(sp 3 ) coupling of amides and α-bromoboronates to access β-aminoboromonates. The mild conditions, such as visible light, room temperature and absence of strong bases, enable the late-stage transformation of complex molecules and good functional group compatibility.…”
Section: Synthetic Applications Of Decatungstate Photocatalysts In Ha...mentioning
confidence: 99%
“…Xu et al 69 reported an effective method for achieving the C(sp 3 )–C(sp 3 ) coupling of amides and α-bromoboronates to access β-aminoboromonates. The mild conditions, such as visible light, room temperature and absence of strong bases, enable the late-stage transformation of complex molecules and good functional group compatibility.…”
Section: Synthetic Applications Of Decatungstate Photocatalysts In Ha...mentioning
confidence: 99%